Clinical-morphological and molecular-genetic features of chronic brain ischemia - Yakubova, Marhamat; Muqaddas, Raxmatova; Dildora, Kushaeva; Nasiba, Yuldasheva (International Journal of Psychosocial Rehabilitation, 2020)
The basis for the development of chronic brain ischemia is a violation of the functional properties of the vascular endothelium, which subsequently leads to a change in vascular tone and disease progression. Changes in the hemodynamic properties of blood and blood pressure also play an important role, which is why the study of genes encoding proteins that are involved in the regulation of water-salt metabolism and maintaining the tone of the vascular wall is of greatest interest. This article presents the association between patients with chronic ischemia with pathological deformities in the internal carotid arteries and ACE gene polymorphism (angiotensin converting enzyme) of the I/D variant, as well as to establish an association with morphological changes in the vascular wall. We comprehensively examined 155 individuals’ data, of which 105 patients with chronic brain ischemia were the main group. The control group of healthy individuals was 50 people. Determination of ACEI / D gene polymorphisms by polymerase chain reaction. Reliable dominance of the D allele and the D / D genotype of the ACE gene with greater occurrence in patients with II stage encephalopathy were established. Morphological changes with severe lesions of the vascular wall were more common in patients with the consequences of a previous ischemic stroke. The data obtained once again confirm the important etiopathogenetic role of molecular genetics mechanisms in the development of chronic brain ischemia with cerebral artery dysplasia.